Association between Women Empowerment and Social Support in the Reproductive Decision-Making of the Women Referring to the Health Centers in Sari, Iran (2017) - Kiani Z; Aghamohammadi A; Zafari M (Zanjan University of Medical Sciences and Health Services, 2018)
Background: Empowerment of women is considered to be a critical developmental strategy. Objectives: Today, empowerment of women is not only a priority, but it also is an urgent need of women as a one of the most important populations considering their roles in the family and community. Social support and empowerment of women are regarded as an investment for future generations, which will result in sustainable development. The present study aimed to explore the association between the social support and empowerment of women with their reproductive decisions in the health centers in Sari, Iran. Methods: This descriptive-correlational study was conducted on 400 women referring to the health centers in Sari, Iran in 2017. The subjects who met the inclusion criteria were selected via multistage cluster sampling. Data were collected using a demographic and reproductive characteristics questionnaire, multidimensional scale of perceived social support, and the questionnaire of women empowerment and reproductive behavior. Data analysis was performed in SPSS version 16. Results: The subjects had a moderate level of empowerment in their reproductive decisions. On the other hand, favorable and poor empowerment levels were observed in the dimensions of cultural background and family planning, respectively. Furthermore, social support had a direct, significant correlation with the empowerment of women in reproductive decisions (P=0.001; r=0.34). Conclusion: According to the results, the empowerment and social support of women are imperative issues that require special attention and investment considering the key role of women in promoting community health.